Hindi-Urdu : sajha sanskriti - Simha, Murali Manohar Prasad (Nai Dilli : Neśanal Buk Trast, Indiya, 2010)
Comparative study of Hindi and Urdu languages and literatures; traces the influence, common elements, and history of both; contributed articles
Na hindskome. Neki članci su prevedeni s urdskoga.
Keywords: hindski jezik - utjecaj na urdski -- urdski jezik - utjecaj na hindski; hindsko-urdske kulturne veze -- poredbena književnost - hindska i urdska